APPRAISAL OF THE EFFECTS OF BIG BROTHER NAIJA REALITY SHOW ON NIGERIA’S CULTURAL HERITAGE AMONG RESIDENTS OF OWERRI METROPOLIS, IMO STATE - Anyanwu, B. J. C.; Ekwerigwe, Amarachi Maryann (African Journal of Social and Behavioural Sciences, 2021)
The study is an appraisal of the effects of “Big Brother Niaja Pepper Them Reality Show” on Nigerian culture among residents of Owerri metropolis. It aimed at determining the level of viewership of BBN Pepper Them Reality Show among Owerri metropolis residents; and Finding out if Big Brother Pepper them Reality show is a plus or minus on Nigeria culture among Owerri metropolis residents. This study was anchored on Cultivation media Theory. The study adopted survey research method. A sample size of 384 was drawn from the population of 1,563,758 using Wimmer and Dominick calculator. Multi-stage sampling technique was used for this study. Questionnaire was used as instruments for data collection. It was fund that there is high viewership level of BBN Pepper Them Reality Show among Owerri metropolis residents; that Big Brother Pepper Them Reality Show is a minus on Nigeria culture and it has no benefits or gratifications to the residents of Owerri metropolis. It was therefore recommended that: Mass education on media ratings and encouraging producers of BBN to adhere to the principles of professional media scheduling, programming and content placement. It was also recommend campaign for restructuring and sustenance of the programme should reflect more indigenous Nigeria cultures and serve as a window to showcase indigenous African culture to the outside world.